Widespread resistance mutations to sulfadoxine-pyrimethamine in malaria parasites imported to China from Central and Western Africa. (April 2020) - Zhao, Luyi; Pi, Liang; Qin, Yucheng; Lu, Yuxin; Zeng, Weilin; Xiang, Zheng; Qin, Pien; Chen, Xi; Li, Cuiying; Zhang, Yanmei; Wang, Siqi; Si, Yu; et al.
Abstract: Background: Imported cases of infectious disease provide invaluable information about epidemiological conditions abroad, and should guide treatment decisions at home and abroad. Here, we examined cases of malaria imported from Africa to China for mutations eroding the efficacy of sulfadoxine-pyrimethamine (SP), sometimes used as an intermittent preventive treatment during for pregnant women and infants. Methods: A total of 208 blood samples were collected from P. falciparum -infected workers who had returned from Western and Central Africa to Guangxi Province Frequency distribution. Samples were analyzed for the mutations in dhfr and dhps genes by PCR -sequencing. The prevalence of dhfr and dhps polymorphisms was analyzed. Among the isolates, polymorphisms were detected in mutants N51I, C59R, S108N and I164L of Pfdhfr and I431V, S436 A/F, A437G, K540 E/N, A581G and A613T of pfdhps . Results: Mutations promoting drug resistance were widespread in this cohort. For pfdhfr and pfdhps, wild types were equally rare among patients returned from Western Africa and Central Africa. A triple-mutant dhfr haplotype was most prevalent (>70%). We report for the first time mutation I164L- dhfr and I431V- dhps in Ghana, and for the first time we found A581G to exceed a clinically-relevant threshold that may counter-indicate current clinical practices. For Pfdhps, the double-mutant IAG KAA was high prevalent haplotype in Ghana, Western Africa. The single-mutant ISG KAA was a majority haplotype in Cameroon. Alarmingly, a "super resistance" quintuple mutant was detected, for the first time, in parasites of West African origin (defined by IAG KAA/IRN I in combination with pfdhps 581G and dhfr I164L). This may limit the efficacy of this drug combination for even intermittent clinical applications. Conclusions: These data are cause for great concern and call for continued surveillance of the efficacy of SP in source and recipient populations, and should be considered when developing treatment policy for imported malaria cases in China and elsewhere. Graphical abstract: Image 1